Frederick Douglass' Narrative of the Life of Frederick Douglass: Between the Expressions of Unpleasant Feeling and Freedom Gaining on Slavery - Ririn Kurnia Trisnawati; Rizki Februansyah (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2008)
Romanticism in America coincided with the period of national expansion and the emergence of a distinctive American voice triggering the American Renaissance. It was exactly when many American writers were able to express Americans’ new expressions such as imaginative expression over emotion and individual, defense of individual potential and individual freedom as they were rarely vocalized during the former era.The upcoming idea of egalitarianism which is based on the American Liberalism urged Afro-American writers to spread out the spirit of freedom and egalitarianism. They describe several stories about living as a slave. Frederick Douglas has a leading role in the abolishment of slavery in the history of America with his masterpiece Narrative of the Life of Frederick Douglass. That is why the researchers want to find out the spirit of the Romanticism by proving how the social background had taken a part in creating well-known narratives.Using the Sociology of Literature approach, this research is assumed to give effect on shaping the meaning of Narrative of the Life of Frederick Douglass, where his work expresses liberalism in the period of Romanticism and could also be used to characterize the Romanticism. That is why literary discussion can not be separated from the issue when and where a work was written. The question when the literature was written is only a part of the discussion about this period including the remarks of the work and the question where it is associated with the society or sociological background where the work was created.Insecure feeling is one main feature of the Romanticism found in Narrative of the Life of Frederick Douglass. Douglass actualizes the correlation of song and slavery where song is depicted as an escape from the insecure feeling as experienced by slaves. The first objective is to show that when a slave is feeling insecure in his surroundings, then he will try to cheer himself up by singing and will become romantic, too. The second one is the strong spirit of the Romanticism thoroughly found in Narrative of the Life of Frederick Douglass that is the spirit of Liberalism – almost all his narratives express his greatest dream of abolishing slavery trademark of his own. Meanwhile, the sociological background reflected in revolutionary movement took place in Douglass’ surroundings and he accidentally experienced it himself. Then, he made his words to set the slaves free and slavery must be abolished for goodness.